Undetection of vector-borne viruses in equids of Galapagos Islands - Zanella, Gina; Beck, Cécile; Valle-Casuso, José-Carlos; Anthony, Madeline; Cruz, Marilyn; Vélez, Alberto; Vinueza, Rommel Lenin; Gonzalez, Gaëlle (Frontiers in Veterinary Science, 2024)
Domestic species, including equids, were introduced in the Galapagos Islands in the XIX century. Equine vector-borne diseases are circulating in South America but their occurrence in the Galapagos Island was unknown. The objective of this study was to detect the occurrence of West Nile virus (WNV), Usutu virus (USUV) and equine infectious anemia virus (EIAV) in the four Galapagos Islands raising equids if they were present at a prevalence > 1%. Serum samples were collected from 411 equids belonging to 124 owners from April to July 2019. All 2 the results were negative to the ELISA tests used suggesting that WNV, USUV and EIAV are not circulating in the equine population of the Galapagos Islands.